(3GdJShjb ef GdefJL Gdi GdeSJgdc (B/s - (3GdMGL, WGQbs; (3QHGjYjI,Ydj hCNQhfs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2010)
(3ebOeI aj GdJShjb, GdHjFI aj GdJShjb, HMhK heYdheGJ GdJShjb, Sdhc GdeSJgdc, Sdhc GdTQGA aj GdShb GdUfGYj, JbSje GdShb, SjGSGJ hbQGQGJ GdSdYI, JWhjQ GdSdY GdLOjOI, CgOGa hSjGSGJ GdJSYjQ, bfhGJ GdJhRjY, eDSSGJ GdJShjb, GdJhRjY GdeGOj, GdJQhjL, GdHjY GdTNUjs
(3JhLO fSNI bOjeI (B1990s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs